1988
DOI: 10.1128/iai.56.7.1800-1806.1988
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Haemophilus influenzae with human erythrocytes and oropharyngeal epithelial cells is mediated by a common fimbrial epitope

Abstract: The role of fimbriae in the adherence of Haemophilus influenzae to oropharyngeal epithelial cells and the hemagglutination (HA) of human Anton-positive erythrocytes was examined. HA of bacteria was lost after shearing. Fimbriae purified from the extracellular fluid caused HA and bound to oropharyngeal epithelial cells, as analyzed with immunoperoxidase staining, in a way which was similar to the adherence of bacteria to these cells: binding was over the entire surface of the cells and showed cell-to-cell varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…On the other hand, human oropharyngeal epithelial cells lack this antigen, and pilus-dependent attachment to these cells is una¡ected by anti-AnWj antiserum [98]. Nevertheless, the same antipilus monoclonal antibody is capable of inhibiting agglutination of erythrocytes and attachment to oropharyngeal epithelial cells, suggesting that pili may recognize the same receptor structure on both erythrocytes and epithelial cells [99]. Consistent with this possibility, experiments with piliated type b and non-typable strains have demonstrated that compounds containing sialyllactosylceramide, including the gangliosides GM1, GM2, GM3, and GD1a, are able to inhibit hemagglutination and adherence to epithelial cells [100].…”
Section: Hemagglutinating Pilimentioning
confidence: 99%
“…On the other hand, human oropharyngeal epithelial cells lack this antigen, and pilus-dependent attachment to these cells is una¡ected by anti-AnWj antiserum [98]. Nevertheless, the same antipilus monoclonal antibody is capable of inhibiting agglutination of erythrocytes and attachment to oropharyngeal epithelial cells, suggesting that pili may recognize the same receptor structure on both erythrocytes and epithelial cells [99]. Consistent with this possibility, experiments with piliated type b and non-typable strains have demonstrated that compounds containing sialyllactosylceramide, including the gangliosides GM1, GM2, GM3, and GD1a, are able to inhibit hemagglutination and adherence to epithelial cells [100].…”
Section: Hemagglutinating Pilimentioning
confidence: 99%
“…The fimbriae are often considered as an adhesine which intermediates the attachment. Also for Haemophilus influenzae type b (Hib) infections in humans it has been described repeatedly that fimbriae take part in the adhesion of the pathogen ( VAN ALPHEN et al, 1988;FARLEY et al, 1990;PATRICK et al, 1989). PICHICHERO et al (1982) reported that fimbriation is general among Hib.…”
mentioning
confidence: 99%
“…Hemagglutination (HA) as a screening test for fimbriaemediated adhesion on gram-negative bacteria is well-known (DUGUID and WILKINSON, 1961). Especially for Hib, VAN ALPHEN et al (1988) andFARLEY et al (1990) reported that the adhesive properties of fimbriae are detectable by hemagglutination with human erythrocytes. Comparative to strain 493 we tested 3 other laboratory strains of H .…”
mentioning
confidence: 99%
“…In this adherence mechanism, there are many reports that adherence of H. influenzae to buccal epithelial cells is most often mediated by fimbriae (1,3). Many workers, however, checked the presence of the fimbriae of H. influenzae by the method of human RBC hemagglutination, and almost all of them did not directly observe the fimbriae under electron microscope.…”
Section: Discussionmentioning
confidence: 99%